Unisexual hybrids break through an evolutionary dead end by two‐way backcrossing. (7th January 2020) - Suzuki, Shota; Miyake, Shota; Arai, Katsutoshi; Munehara, Hiroyuki
Abstract: Unisexual vertebrates (i.e., those produced through clonal or hemiclonal reproduction) are typically incapable of purging deleterious mutations, and, as a result, are considered short‐lived in evolutionary terms. In hemiclonal reproduction (hybridogenesis), one parental genome is eliminated during oogenesis, producing haploid eggs containing the genome of a single parent. Hemiclonal hybrids are usually produced by backcrossing hemiclonal hybrids with males of the paternal species. When hemiclonal hybrids from a genus of greenlings ( Hexagrammos ) are crossed with males of the maternal species, the progeny are phenotypically similar to the maternal species and produce recombinant gametes by regular meiosis. The present study was conducted to determine if the hemiclonal genome is returned to the gene pool of the maternal species in the wild. Using a specific cytogenetic marker to discriminate between such progeny and the maternal species, we observed that Hexagrammos hybrids mated with maternal and paternal ancestors at the same frequency. This two‐way backcrossing in which clonal genomes are returned to the gene pool where they can undergo recombination plays an important role in increasing the genetic variability of the hemiclonal genome and reducing the extinction risk. In this way, hybrid lineages may have survived longer than predicted through occasional recombinant generation.